2008
DOI: 10.1007/s10620-008-0630-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Colitis Due to Glutaraldehyde: Case Series and Review of the Literature

Abstract: Chemical colitis can occur as a result of accidental contamination of endoscopes or by intentional/accidental administration of enemas containing various chemicals.We present three cases of glutaraldehyde induced colitis and review the cases in the literature. Glutaraldehyde induced colitis presents clinically with severe abdominal pain, bloody and mucoid diarrhea, rectal bleeding, and tenesmus 48-72 h after colonoscopy. Endoscopic findings are nonspecific and mimic ischemic colitis, inflammatory bowel disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Gutterman et al [209] identified only eight studies "which reported numerous adverse outcomes to healthcare personnel associated with endoscope reprocessing", including one case report with asthma for workers using a peracetic acid and hydrogen peroxide based product. The most commonly-reported side effect of peracetic acid in patients is a form of colitis, previously known as pseudolipomatosis [210] , which is commonly induced by hydrogen peroxide and peracetic acid but occasionally also by glutaraldehyde [211] . The colitis is often self-limiting but sometimes requires medical treatment.…”
Section: Clinical Side Effects Of Peracetic Acidmentioning
confidence: 99%
“…Gutterman et al [209] identified only eight studies "which reported numerous adverse outcomes to healthcare personnel associated with endoscope reprocessing", including one case report with asthma for workers using a peracetic acid and hydrogen peroxide based product. The most commonly-reported side effect of peracetic acid in patients is a form of colitis, previously known as pseudolipomatosis [210] , which is commonly induced by hydrogen peroxide and peracetic acid but occasionally also by glutaraldehyde [211] . The colitis is often self-limiting but sometimes requires medical treatment.…”
Section: Clinical Side Effects Of Peracetic Acidmentioning
confidence: 99%
“…This finding is considered to be important for applying ESW to disinfection method in clinical settings. High-level disinfectants, such as glutaraldehyde (GA), have disinfection potentials against any microorganisms; however, it has been reported that it may be harmful to patients and healthcare workers (1,2). ESW is considered less toxic than GA (13), and it has been reported to be effective against disinfectantresistant bacteria, such as Pseudomonas aeruginosa (6), spore-forming bacteria (3,4,6), and bloodborne infectious pathogens such as hepatitis B virus (8,11) and HIV (5) depending on the condition.…”
Section: -10mentioning
confidence: 99%
“…Splenic hematoma and rupture, intramural hematoma, subcutaneous emphysema in the absence of frank colonic perforation, tearing of mesenteric vessels with intra-abdominal bleeding, thrombosis in carotid-subclavian artery bypass graft, thrombophlebitis in the intravenous site, intestinal obstruction, and ischemic and chemical colitis secondary to glutaraldehyde or air insufflation have been reported following colonoscopy in literature [3,14,15,23,31,57,58].…”
Section: Miscellaneousmentioning
confidence: 99%